Organic-inorganic interpenetrating heat prevention and insulation integrated material and in-situ preparation method thereof

By using organic and inorganic interpenetrating heat insulation integrated materials in the thermal protection system, the in-situ curing technology of phosphate and boron modified phenolic resins is used to form a porous skeleton and topological network-like carbonized layer structure, the problems of insufficient ablation and thermal insulation performance of existing materials are solved, and efficient thermal protection effect is achieved.

CN119899423AActive Publication Date: 2025-04-29CENT SOUTH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510376588.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-29
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The existing thermal protection system materials have low ablation resistance and thermal insulation properties, and the matrix interface bonding force is insufficient, making it difficult to maintain the integrated thermal insulation function in an extreme thermal-force coupling environment.

Method used

The organic and inorganic interpenetrating heat-insulating integrated material is adopted. This material is formed by in-situ pressurization of phosphate slurry and boron-modified phenolic resin to form a porous skeleton, and the surface is brushed with phosphate slurry II for normal pressure curing to form a tightly bonded topological network carbonized layer structure.

Benefits of technology

It significantly improves the interface bonding force of the material, ablation resistance and heat insulation performance, and can effectively prevent ablation and heat conduction in low-oxygen and high-temperature environments, protecting the material structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899423A_ABST
    Figure CN119899423A_ABST
Patent Text Reader

Abstract

The invention discloses an organic-inorganic interpenetrating heat prevention and insulation integrated material and an in-situ preparation method thereof, and belongs to the field of preparation of ablation-resistant materials. The material comprises porous skeletons and a phosphate slurry II normal-pressure curing coating, wherein the porous skeletons are formed by phosphate slurry I and boron modified phenolic resin through in-situ pressurization and curing, and the phosphate slurry II normal-pressure curing coating is brushed on the surfaces of the porous skeletons; the phosphate slurry I and the phosphate slurry II are formed by stirring raw materials including aluminum dihydrogen phosphate and nano zirconium oxide; the mass fraction of the nano zirconium oxide in the phosphate slurry II is greater than that of the nano zirconium oxide in the phosphate slurry I. Through the synergistic effect of the composition and the structure, the material has the characteristic of high matrix interface bonding force and excellent ablation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an organic-inorganic interpenetrating heat-insulating integrated material and an in-situ preparation method thereof, and belongs to the field of preparation of ablation-resistant materials. Background Art

[0002] In recent years, with the development of aerospace technology and the deepening of deep space exploration, the significant increase in the flight speed of spacecraft has led to an increasingly harsh re-entry environment. When the return capsule passes through the dense atmosphere at a speed of several thousand meters per second, the intense aerodynamic heating can cause the surface temperature to rise sharply to over 2000°C. If there is a lack of efficient thermal protection measures, the return capsule structure will face the risk of ablation and disintegration. In order to ensure the safety of astronauts and the reliability of equipment, improving the ablation resistance and thermal insulation performance of the thermal protection system (TPS) has become a core technical bottleneck that needs to be broken through in the aerospace field.

[0003] However, traditional metal-based and ceramic-based thermal insulation materials are gradually unable to meet the requirements of lightweight and integrated design due to defects such as high density, high brittleness, and poor processing adaptability. Although polymer-based composite materials dominate TPS key components such as the combustion chamber of the propellant ramjet engine (PRE) and the throat of the rocket nozzle due to their low density, excellent mechanical properties and heat resistance, they still have obvious limitations, such as: the interface bonding strength between the resin matrix and the inorganic filler is insufficient, and interface stratification is prone to occur at high temperatures; traditional laminated composite structures are prone to thermal stress concentration in extreme thermal-mechanical coupling environments, resulting in the failure of the integrated thermal insulation function. In addition, the existing material system is difficult to take into account the synergistic improvement of ablation protection and thermal insulation performance, which restricts the technological development of the new generation of hypersonic aircraft. Summary of the invention

[0004] In view of the problems of low ablation resistance and thermal insulation performance, poor matrix interface bonding ability and other problems of thermal protection system materials in the prior art, the first purpose of the present invention is to provide an organic-inorganic interpenetrating thermal insulation integrated material, in which the resin-based organic components and the phosphate inorganic components are interspersed and tightly combined with each other, which not only solves the problem of low matrix interface bonding strength, but also forms a topological network carbonization layer structure in situ through carbonization reaction in a low oxygen and high temperature environment, and synergistically with the boron element introduced in the zirconium oxide particles and boron phenolic resin, effectively solves the shortcomings of high-temperature failure of traditional structural integrated thermal insulation materials.

[0005] The second object of the present invention is to provide a method for preparing an organic-inorganic interpenetrating anti-insulation integrated material. The method prepares organic components, inorganic components and pore-forming agents in situ to form an organic-inorganic interpenetrating and internally porous structure, which significantly enhances the interfacial bonding force of the components. The preparation process is simple, the reagents and raw materials are cheap and easy to obtain, the preparation cycle is short, the preparation equipment and conditions are simple, and it is conducive to large-scale industrial production.

[0006] In order to achieve the above technical objectives, the present invention provides an organic-inorganic interpenetrating anti-heat-insulating integrated material, which includes a porous skeleton with mutual interpenetration distribution formed by in-situ pressure curing of phosphate slurry I and boron-modified phenolic resin, and a phosphate slurry II normal pressure curing coating brushed on the surface of the porous skeleton; the phosphate slurry I and phosphate slurry II are both formed by stirring raw materials including dihydrogen aluminum phosphate and nano zirconium oxide; and the mass fraction of nano zirconium oxide in phosphate slurry II is greater than the mass fraction of nano zirconium oxide in phosphate slurry I, and the porosity of the organic-inorganic interpenetrating anti-heat-insulating integrated material is 35~40%.

[0007] The key to the excellent interface bonding force and excellent heat insulation and ablation resistance of the material of the present invention lies in the simultaneous existence of organic and inorganic components and the synergistic effect of interpenetration and porous structure.

[0008] The principle of ablation resistance of the material of the present invention is derived from a multi-stage synergistic mechanism. Specifically, at the initial stage of ablation, the surface of the material rapidly absorbs heat and the temperature rises sharply. First, the aluminum phosphate monohydrate phase (formed by the reaction of aluminum dihydrogen phosphate and nano zirconium oxide) present in the phosphate slurry II is dehydrated and melted at high temperature, and the aluminum dihydrogen phosphate phase is also decomposed due to high temperature. The two take away part of the heat, and a small amount of heat is transferred to the upper layer inside the material. Then the sub-surface of the boron phenolic resin preferentially undergoes step-by-step pyrolysis, releasing gases such as H2O, CO, and CO2. At this time, the decomposition of the surface phosphate and the decomposition of the sub-surface boron phenolic acid resin take away a large amount of initial heat, reducing the continuous penetration of heat and the degree of ablation damage on the surface of the material. As the temperature further increases, the aluminum phosphate formed after dehydration melts and sinks, and the molten aluminum phosphate and other substances sink to fill the surface and internal pore structure of the material, preventing the penetration of oxygen, and at the same time providing heat for further carbonization and other reactions of organic matter in the sub-surface of the material. Organic matter with an interpenetrating network structure undergoes a carbonization reaction in a low-oxygen and high-temperature environment, forming a topological network carbonization layer structure in situ. On the one hand, the carbon content of the carbonized layer is relatively high, and the presence of carbon ensures that the material maintains a certain structural stability at high temperatures; on the other hand, the carbonized layer is a porous structure, and the pores can hinder heat conduction, just like a thermal insulation barrier, reducing the transfer of heat to the inside of the material and protecting the matrix. The stable topological network carbonized layer structure can not only effectively fix the molten aluminum phosphate to prevent its diffusion, but also prevent the material from ablating and retreating. As the ablation continues, the boron element in the boron phenolic resin reacts with other substances at high temperatures to produce compounds such as B2O3. These compounds further react with carbon to produce B4C, etc., and finally form a ceramic layer composed of B4C, B2O3 and glassy carbon in the topological network carbonized layer structure, further improving the high temperature resistance and thermal insulation properties of the carbonized layer. At the same time, the zirconium oxide particles on the surface sinter and grow at high temperatures, acting as pinning to fix the dissipation of the molten aluminum phosphate. In the later stage of ablation, a zirconium oxide particle layer, molten aluminum oxide and other substances, a topological network carbonized layer structure, and the lower original material and porous structure layer are formed from top to bottom. The specific structure is as follows: Figure 7 As shown. Due to the high temperature resistance of the surface zirconia, the material exhibits excellent high temperature ablation resistance; similarly, the pore structure left by the pore former inside the material can effectively reduce the heat transfer efficiency, thereby exhibiting excellent high temperature thermal insulation performance.

[0009] At the same time, in the present invention, the mass fraction of nano zirconium oxide in phosphate slurry II is greater than the mass fraction of nano zirconium oxide in phosphate slurry I. The reason for this arrangement is that zirconium oxide has a high melting point and is the main material for resisting ablation of the material system. The amount of zirconium oxide added in the phosphate II on the surface of the brush coating is relatively large, and a zirconium oxide layer can be formed on the surface in subsequent ablation experiments to protect the material's internal material, so that the internal structure of the solid carbon layer is better formed to further improve the ablation stability and reliability. The reason why zirconium oxide is less in the phosphate slurry I used for the interpenetrating organic-inorganic material prepared in situ is that a large amount of high melting point phases are not required internally, and the zirconium oxide particles that are not ablated internally can play a toughening role, and its excessive addition will affect the thermal insulation performance of the material. And the outer surface of the material of the present invention has no holes, but the internal skeleton structure has a higher porosity, which is conducive to hindering heat conduction in the middle and late stages of ablation, like a thermal insulation barrier, reducing heat transfer to the inside of the material, and protecting the matrix.

[0010] As a preferred solution, the mass ratio of the phosphate slurry I, the boron-modified phenolic resin and the phosphate slurry II is (40-80): (2-8): (10-15). If the amount of phosphate slurry I added is too much, the organic-inorganic interpenetrating structure will be reduced, making it difficult to form a topological network carbonized layer structure, resulting in uneven distribution of the carbon layer inside the system, affecting the anti-ablation support and thermal insulation performance; if the phosphate slurry is too large, the organic-inorganic interpenetrating structure will be reduced, making it difficult to form a topological network carbonized layer structure, resulting in uneven distribution of the carbon layer inside the system, affecting the anti-ablation support and thermal insulation performance; The amount of addition is small, and the proportion of organic matter in the matrix is ​​high. During high-temperature ablation, a large amount of organic matter near the ablation layer will be carbonized and volatilized. First, the mass ablation rate will be seriously reduced. Secondly, the dense zirconium oxide layer of the ablation layer will be seriously damaged, forming more external exhaust holes. Oxygen molecules penetrate and cause the carbon layer to fail due to oxidation. The effect of boron-modified phenolic resin is similar to that of phosphate slurry I. Too much brushing of phosphate slurry II will increase the coating thickness and reduce the organic-inorganic hybrid layer of the matrix. Since the brushed phosphate slurry II has a dense non-porous structure and its thermal conductivity is greater than that of the matrix material, it will seriously affect the ablation back temperature at the same ablation temperature; and if the amount of phosphate slurry II brushed is reduced, the surface coating will be thin. In the subsequent ablation, the phosphate decomposes and volatilizes to form small holes. The ablation flame directly destroys the matrix, affecting the overall ablation performance of the material.

[0011] As a preferred solution, the viscosity of the phosphate slurry I is 10-15 Pas, and the viscosity of the phosphate slurry II is 15-20 Pas.

[0012] As a preferred solution, the mass ratio of aluminum dihydrogen phosphate and nano zirconium oxide in the phosphate slurry I is (1-3): (2-5); a further preferred mass ratio of aluminum dihydrogen phosphate and nano zirconium oxide is (1-2): (2-3).

[0013] As a preferred solution, the mass ratio of aluminum dihydrogen phosphate to nano zirconium oxide in the phosphate slurry II is (1-3): (2-6).

[0014] The preferred range of the mass ratio of aluminum dihydrogen phosphate to nano zirconium oxide in phosphate slurry I and phosphate slurry II of the present invention is conducive to maintaining the stability of the material structure and the gradient heat-insulating performance of the outer surface layer and the internal material during the ablation process.

[0015] The present invention also provides a method for preparing an organic-inorganic interpenetrating anti-heat-insulating integrated material, which comprises mixing raw materials including phosphate slurry I, boron-modified phenolic resin and pore-forming agent, pouring the mixture into a mold, performing pressurized heating and curing to obtain a porous skeleton; and brushing phosphate slurry II on the outer surface of the porous skeleton and curing the mixture at normal pressure to obtain the obtained material.

[0016] The preparation method of the present invention forms an integral body by in-situ curing of phosphate slurry I, boron-modified phenolic resin and pore-forming agent through high cohesiveness and good compatibility of phosphate and resin base, and the pore-forming agent is pyrolyzed and forms a pore structure during high temperature curing, thereby forming an organic and inorganic porous skeleton interpenetrating each other in situ, significantly improving the interface bonding force. The surface pore structure can be sealed by brushing phosphate slurry II, avoiding direct contact of subsequent ablation with organic matter, and protecting the internal structure. The boron-modified phenolic resin used in the present invention is to introduce boron element into the molecular structure of phenolic resin to replace hydrogen in phenolic hydroxyl group, and because the bond energy of boron oxygen bond is higher than carbon carbon bond, a three-dimensional network structure containing boron is formed in application, further improving the ablation resistance of the material.

[0017] The pore-forming agent used in the present invention is an inorganic pore-forming agent commonly used in the market, such as ammonium bicarbonate, ammonium carbonate, etc.

[0018] As a preferred solution, the mass ratio of the phosphate slurry I, the boron-modified phenolic resin and the pore-forming agent is (40-80): (2-8): (1-4). If the amount of the pore-forming agent added is large, the matrix material will have more pore structures, which will affect the overall mechanical properties of the material and thus affect the ablation reliability; if the amount of the pore-forming agent added is small, fewer pore structures will be formed inside the matrix, which will affect the subsequent ablation thermal insulation performance and cause the back temperature of the material to increase. Further preferably, the mass ratio of the phosphate slurry I, the boron-modified phenolic resin and the pore-forming agent is (40-60): (2-6): (1-2).

[0019] As a preferred solution, the conditions for the pressurized heating curing molding are: temperature of 120-150°C and pressure of 2-15Mpa. In this temperature range, the boron phenolic resin partially melts and can be well combined with the phosphate material, and by appropriate pressurization, the phosphate slurry I and the boron modified phenolic resin can be more closely combined, and in-situ composite curing molding can be achieved. It is further preferred that the temperature is 120-130°C and the pressure is 5-10Mpa.

[0020] As a preferred solution, the molding time of the pressurized heating and curing molding is 1 to 5 hours, and more preferably, the molding time is 2 to 4 hours.

[0021] As a preferred solution, the pressurized and heated equipment selected in the present invention can use a flat vulcanizing agent.

[0022] As a preferred solution, the brush coating is applied in small amounts and multiple times until the pores on the surface of the porous skeleton are sealed, thereby preventing subsequent ablation from directly contacting organic matter and protecting the internal structure.

[0023] As a preferred solution, after applying phosphate slurry II, it is shaken and then placed in an oven for curing and molding. The further shaking frequency is 100-150 / min, and the further preferred shaking frequency is 100-120 / min, and the shaking time is 2-6min.

[0024] As a preferred solution, the temperature of the normal pressure curing molding is 80-100° C. The normal pressure curing molding of the present invention is mainly to solidify the phosphate slurry II applied by brush.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The organic-inorganic interpenetrating thermal insulation integrated material provided by the present invention has a resin-based organic component and a phosphate inorganic component interpenetrating with each other and tightly combined together, which not only solves the problem of low matrix interface bonding strength, but also forms a topological network carbonization layer structure in situ by carbonization reaction in a low oxygen and high temperature environment. The boron element introduced in the zirconia particles and boron phenolic resin effectively solves the shortcoming of high temperature failure of traditional structural integrated thermal insulation materials.

[0027] (2) The present invention prepares the organic component, the inorganic component and the pore-forming agent in situ and solidifies them in one step to form an organic-inorganic interpenetrating structure with internal pores, which significantly enhances the interfacial bonding force of the components. The preparation process is simple, the reagents and raw materials are cheap and easy to obtain, the preparation cycle is short, the preparation equipment and conditions are simple, and it is conducive to large-scale industrial production.

[0028] (3) The zirconium oxide particles in the material of the present invention will sinter and grow at high temperatures to act as pins to fix the dissipation of molten aluminum phosphate, thereby improving the stable structure of the material.

[0029] (4) During the ablation process, the boron element introduced into the boron phenolic resin forms a ceramic layer composed of B4C, B2O3 and glassy carbon in the topological network carbonized layer structure, further improving the high temperature resistance and heat insulation performance of the carbonized layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a surface microscopic morphology of the material after curing using a flat vulcanizer in Example 1 (before applying phosphate slurry II).

[0031] Figure 2 This is a data chart of the compressive strength of the organic-inorganic interpenetrating thermal insulation integrated material prepared in Example 1.

[0032] Figure 3 This is a surface microscopic morphology of the material of Example 2 after curing using a flat vulcanizer (before applying phosphate slurry II).

[0033] Figure 4 The XRD data of the material in Example 2 after being cured using a flat vulcanizer (before applying phosphate slurry II).

[0034] Figure 5 This is a surface microscopic morphology of the organic-inorganic interpenetrating anti-thermal insulation integrated material prepared in Example 2.

[0035] Figure 6 This is a data chart of the compressive strength of the organic-inorganic interpenetrating thermal insulation integrated material prepared in Example 2.

[0036] Figure 7 This is a surface microscopic morphology of the organic-inorganic interpenetrating anti-thermal insulation integrated material prepared in Example 2 after being ablated at 2500°C.

[0037] Figure 8 This is a cross-sectional microscopic morphology of the organic-inorganic interpenetrating thermal insulation integrated material prepared in Example 2 after ablation at 2500°C.

[0038] Fig. 9 This is a schematic structural diagram of the material formed after the organic-inorganic interpenetrating anti-heat-insulation integrated material prepared by the present invention is ablated at 2500°C.

[0039] Fig.10 This is a data chart of the compressive strength of the organic-inorganic interpenetrating thermal insulation integrated material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0040] In order to further illustrate the present invention, the contents of the present invention are described in detail below in conjunction with the examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following examples.

[0041] The boron-modified phenolic resin used in the examples and comparative examples of the present invention was purchased from Chenghui New Materials and its product model is PF-241.

[0042] Example 1

[0043] (1) Mix 20 g of aluminum dihydrogen phosphate solution and 40 g of nano zirconium oxide particles, and stir for 0.4 h to obtain phosphate slurry I;

[0044] (2) Weigh 40 g of the phosphate slurry I obtained in step 1, mix with 4 g of boron-modified phenolic resin and 1 g of pore-forming agent (ammonium bicarbonate), stir for 0.3 h, pour into a mold, place in a flat plate vulcanizer at 120°C, mold at 8 MPa and maintain pressure for 3 h to obtain a porous skeleton;

[0045] (3) Mix 20 g of aluminum dihydrogen phosphate solution and 55 g of nano zirconium oxide particles, and stir for 0.2 h to obtain phosphate slurry II;

[0046] (4) The phosphate slurry II obtained in step 3 was brushed onto the porous skeleton surface of step 2, with a brushing amount of 10 g. After oscillation at 110 times / min for 5 min, the mixture was placed in an oven at 80°C for curing to obtain an organic-inorganic interpenetrating anti-thermal insulation integrated material with a porosity of 37%.

[0047] In the subsequent ablation experiment, the mass ablation rate and line ablation rate of the material were 0.0093g / s and 0.013mm / s respectively. The ablation surface temperature was 2480℃ and the back temperature was 152℃. Its compressive strength reached 5.13MPa, indicating that the material has good bonding and is not easy to be damaged.

[0048] Example 2

[0049] (1) Mix 20 g of aluminum dihydrogen phosphate solution and 50 g of nano zirconium oxide particles, and stir for 0.3 h to obtain phosphate slurry I;

[0050] (2) Weigh 40 g of the phosphate slurry I obtained in step 1, mix it with 6 g of boron-modified phenolic resin and 1 g of pore-forming agent (ammonium bicarbonate), stir it for 0.3 h, pour it into a mold, place it in a flat plate vulcanizer at 120°C, mold it at 8 MPa and maintain it at a pressure of 3 h to cure it, and obtain a porous skeleton;

[0051] (3) Mix 20 g of aluminum dihydrogen phosphate solution and 60 g of nano zirconium oxide particles, and stir for 0.2 h to obtain phosphate slurry II;

[0052] (4) The phosphate slurry II obtained in step 3 was brushed onto the porous skeleton surface of step 2, with a brushing amount of 12 g. After oscillation at 120 times / min for 5 min, the mixture was placed in an oven at 80°C for curing to obtain an organic-inorganic interpenetrating anti-thermal insulation integrated material with a porosity of 37%.

[0053] In the subsequent ablation experiment, the mass ablation rate and line ablation rate of the material were 0.0085g / s and 0.016mm / s respectively. The ablation surface temperature was 2480℃ and the back temperature was 135℃. Its compressive strength reached 6.15MPa, indicating that the material has good bonding and is not easy to be damaged.

[0054] Example 3

[0055] (1) Mix 25 g of aluminum dihydrogen phosphate solution and 70 g of nano zirconium oxide particles, and stir for 0.3 h to obtain phosphate slurry I;

[0056] (2) Weigh 50 g of the phosphate slurry I obtained in step 1, mix it with 5 g of boron-modified phenolic resin and 2 g of pore-forming agent (ammonium bicarbonate), stir it for 0.3 h, pour it into a mold, place it in a flat plate vulcanizer at 130°C, mold it at 9 MPa and maintain it for 2 h to cure it, and obtain a porous skeleton;

[0057] (3) mixing 10 g of aluminum dihydrogen phosphate solution and 40 g of nano zirconium oxide particles to obtain phosphate slurry II;

[0058] (4) The phosphate slurry II obtained in step 3 was brushed onto the surface of the porous skeleton in step 3, with a brushing amount of 13 g. After oscillation at 120 times / min for 6 min, it was placed in an oven at 80°C for curing to obtain an organic-inorganic interpenetrating anti-thermal insulation integrated material with a porosity of 38%.

[0059] In subsequent ablation experiments, the mass ablation rate and line ablation rate of the material were 0.0081g / s and 0.017mm / s respectively. The ablation surface temperature was 2450℃ and the back temperature was 149℃.

[0060] Example 4

[0061] (1) Mix 25 g of aluminum dihydrogen phosphate solution and 70 g of nano zirconium oxide particles, and stir for 0.3 h to obtain phosphate slurry I;

[0062] (2) Weigh 50 g of the phosphate slurry I obtained in step 1, mix it with 5 g of boron-modified phenolic resin and 2 g of pore-forming agent (ammonium carbonate), stir it for 0.3 h, pour it into a mold, place it in a flat plate vulcanizer at 150°C, press it at 3 MPa for 2 h, and solidify it to obtain a porous skeleton;

[0063] (3) mixing 10 g of aluminum dihydrogen phosphate solution and 40 g of nano zirconium oxide particles to obtain phosphate slurry II;

[0064] (4) The phosphate slurry II obtained in step 3 was brushed onto the surface of the porous skeleton in step 3, with a brushing amount of 15 g. After oscillation at 120 times / min for 6 min, it was placed in a 90°C oven for curing to obtain an organic-inorganic interpenetrating anti-thermal insulation integrated material with a porosity of 39%.

[0065] In subsequent ablation experiments, the mass ablation rate and line ablation rate of the material were 0.0083g / s and 0.011mm / s respectively. The ablation surface temperature was 2527℃ and the back temperature was 168℃.

[0066] Comparative Example 1

[0067] The only difference between this comparative example and Example 2 is that no pore-forming agent is added, and the remaining steps and conditions are the same, thereby obtaining an organic-inorganic interpenetrating integrated material.

[0068] The thermal insulation performance of the composite material is relatively reduced during the ablation process. Since the composite material is prepared by molding on a flat vulcanizer and no pore-forming agent is added, the density of the sample is increased and the porosity is low. The dense sample provides certain convenient conditions for ablation heat conduction, resulting in reduced thermal insulation performance of the sample.

[0069] In subsequent ablation experiments, the thermal insulation performance of this material was poor, with a surface temperature of 2470°C and a back temperature of 311°C. Its thermal insulation performance dropped significantly.

[0070] Comparative Example 2

[0071] The only difference between this comparative example and Example 2 is that there is no flat-plate vulcanizer molding, but oven curing is adopted. The curing temperature is the same as that of Example 2, and the remaining steps and conditions are the same, thereby obtaining an organic-inorganic interpenetrating anti-heat-insulating integrated material.

[0072] The composite material is cured under normal pressure, and the bonding degree between organic and inorganic substances is low, which affects the mechanical properties of the material. In the subsequent ablation performance study, the material is prone to ablation and peeling. Fig.10 Its compressive strength is only 1.47MPa, which affects the reliability of the subsequent experimental environment.

[0073] Comparative Example 3

[0074] The only difference between this comparative example and Example 2 is that the organic matter is replaced by a phenolic resin that is not modified by boron, and the remaining steps and conditions are the same, thereby obtaining an organic-inorganic interpenetrating integrated material.

[0075] Since the added organic matter is unmodified phenolic resin, the composite material has a relatively lower decomposition temperature and carbonization rate. After the organic matter is decomposed, no B2O3 and other substances are generated inside before carbonization, which will affect the subsequent topological network carbonization layer formation and cause ablation to appear ablation retreat. After the material is subsequently ablated at 2485℃, its mass ablation rate and line ablation rate are 0.0081g / s and 0.055mm / s respectively, and its line ablation rate is relatively large.

[0076] Comparative Example 4

[0077] The only difference between this comparative example and Example 2 is that the preparation of phosphate slurry II is to mix 20g of aluminum dihydrogen phosphate solution and 30g of nano zirconium oxide particles, and the other steps and conditions are the same, and an organic-inorganic interpenetrating integrated material is obtained.

[0078] The composite material reduces the content of zirconium oxide in the brush-coated phosphate slurry II. Due to the reduction of zirconium oxide in the coating (anti-ablation layer), in the subsequent ablation experiment, the density and thickness of the zirconium oxide layer on the ablation surface decreased, and the ablation temperature could more easily reach the inside of the material, resulting in an ablation surface temperature of 2450°C, a back temperature of 277°C, and a mass ablation rate and a line ablation rate of 0.0121 g / s and 0.046 mm / s, respectively, which are both relatively large.

Claims

1. An organic-inorganic interpenetrating heat-insulating integrated material, characterized in that: It comprises a porous framework interpenetrating with each other formed by in-situ pressurized curing of phosphate slurry I and boron-modified phenolic resin, and a phosphate slurry II normal pressure curing coating brushed on the surface of the porous framework; The phosphate slurry I and the phosphate slurry II are both formed by stirring raw materials including aluminum dihydrogen phosphate and nano zirconium oxide; And the mass fraction of nano zirconium oxide in phosphate slurry II is greater than the mass fraction of nano zirconium oxide in phosphate slurry I; The porosity of the organic-inorganic interpenetrating heat-insulating integrated material is 35-40%.

2. The organic-inorganic interpenetrating heat-insulating integrated material according to claim 1, characterized in that: The mass ratio of the phosphate slurry I, the boron-modified phenolic resin and the phosphate slurry II is (40-80): (2-8): (10-15).

3. The organic-inorganic interpenetrating heat-insulating integrated material according to claim 2, characterized in that: The mass ratio of aluminum dihydrogen phosphate and nano zirconium oxide in the phosphate slurry I is (1-3): (2-5); The mass ratio of aluminum dihydrogen phosphate to nano zirconium oxide in the phosphate slurry II is (1-3): (2-6).

4. The method for preparing an organic-inorganic interpenetrating heat-insulating integrated material according to any one of claims 1 to 3, characterized in that: The raw materials including phosphate slurry I, boron-modified phenolic resin and pore-forming agent are mixed and poured into a mold for pressurized heating and curing to obtain a porous skeleton; the phosphate slurry II is brushed on the outer surface of the porous skeleton and then cured at normal pressure to obtain the porous skeleton.

5. The method for preparing an organic-inorganic interpenetrating heat-insulating integrated material according to claim 4, characterized in that: The mass ratio of the phosphate slurry I, the boron-modified phenolic resin and the pore-forming agent is (40-80): (2-8): (1-2).

6. The method for preparing an organic-inorganic interpenetrating heat-insulating integrated material according to claim 4, characterized in that: The conditions for the pressurized heating curing molding are: a temperature of 120-150° C. and a pressure of 2-15 Mpa.

7. The method for preparing an organic-inorganic interpenetrating heat-insulating integrated material according to claim 5 or 6, characterized in that: The molding time of the pressurized heating and curing molding is 1 to 5 hours.

8. The method for preparing an organic-inorganic interpenetrating heat-insulating integrated material according to claim 7, characterized in that: The brush coating is performed in small amounts and multiple times until the pores on the surface of the porous skeleton are filled.

9. The method for preparing an organic-inorganic interpenetrating heat-insulating integrated material according to claim 4, characterized in that: The temperature of the normal pressure curing molding is 80-100°C.

Citation Information

Patent Citations

  • High-strength high-temperature-resistant thermal insulation material and preparation method thereof

    CN115572183A

  • Variable-gradient ablation-resistant heat-prevention and heat-insulation integrated phosphate composite material and preparation method thereof

    CN117024163A

  • Ablation-resistant heat-prevention and heat-insulation integrated boron modified phosphate material and preparation method thereof

    CN117902895A

  • Heat prevention and insulation integrated organic-inorganic hybrid phosphate composite material and preparation method thereof

    CN118684477A

  • High heat distortion resistant inorganic laminate

    US20080063875A1